2013
DOI: 10.1177/1350650113508103
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the dry sliding friction and wear behavior of AA6351-SiC-B4C hybrid metal matrix composites

Abstract: In the present study, the effect of wear test parameters on dry sliding wear behavior of aluminum matrix alloy (AA6351) with 5 wt% silicon carbide and 5 wt% boron carbide-reinforced hybrid metal matrix composites was investigated. Wear performance of the hybrid composites was evaluated over an applied load range of 20-100 N and sliding velocities ranging from 1 to 5 m/s. The experimental results show that the hybrid composites retain the wear resistance properties up to load of 60 N and sliding velocities rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Moreover, the mechanical and thermal properties of AMMCs are augmented with the accumulation of particulate reinforcement such as B 4 C, SiC, TiC, Al 2 O 3 , Si 3 N 4 and ZrB 2 and, furthermore, by accretion of secondary particulate reinforcement such as Al 2 O 3 , graphite and BN. The tribological properties of AMMCs were distended [5]. By addition of more than one particulate reinforcement in AMMCs is known as aluminium hybrid metal matrix composites (AHMMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanical and thermal properties of AMMCs are augmented with the accumulation of particulate reinforcement such as B 4 C, SiC, TiC, Al 2 O 3 , Si 3 N 4 and ZrB 2 and, furthermore, by accretion of secondary particulate reinforcement such as Al 2 O 3 , graphite and BN. The tribological properties of AMMCs were distended [5]. By addition of more than one particulate reinforcement in AMMCs is known as aluminium hybrid metal matrix composites (AHMMCs).…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement particles were also preheated at higher temperatures around 1000 C to 1200 C to oxidize their surfaces [14]. The average sizes of the SiC and B 4 C particles were found to be 69 and 149 mm, respectively.…”
Section: Materials Fabricationmentioning
confidence: 99%
“…B4C on the wear performance and mechanical properties of Al 7075-B4C composites were investigated by Baradeswaran and Elaya Perumal. They observed that increasing B4C particles increase the wear performance of the composites when compared to the matrix alloy [9].…”
Section: Ic4m 2018mentioning
confidence: 99%